DISTANCE AIR MONITORING - CERNECKY, Jozef; KONIAR, Jan (Trends in education, 2008)
For air quality evaluation distance monitoring methods are often needed. For this purpose a laser with detecting equipments is mostly used where its narrow beam of electromagnetic radiation in interaction with atmospheric pollutants gives us both quality and quantity information.
Keywords: LIDAR; LASER; distance air monitoring.